A survey of reported behaviours, attitudes and knowledge related to antibiotic use of hospitalised patients in Thailand - Nantanit Sutthiruk (2019)
© 2018 Australasian College for Infection Prevention and Control Background: Inappropriate antibiotic use is a major driver of antimicrobial resistance especially in Thailand where people have access to antibiotics without prescription. Consumers may put pressure on clinicians to prescribe antibiotics when they are not necessary, however little is known about Thai patients’ expectations. The aim of this study was to explore hospitalised patients’ reported behaviours, attitudes and knowledge related to antibiotic use. Methods: A cross-sectional survey was distributed to patients from selected medical and surgical wards at a 1000-bed university hospital in Bangkok between January and March 2016, Thailand. A total of 205 patients participated. Results: The frequent use of antibiotics in the Thai community, misconceptions about the utility of antibiotics in viral illness, and over the counter acquisition of antibiotics were reported. During hospitalisation, patients were unsure whether they wanted antibiotics but if required, intravenous antibiotics were preferred with 84.0% believing that intravenous antibiotics were stronger. The majority wanted to know more about safe antibiotic use and feared acquiring antimicrobial resistant infections. Conclusion: The results of this study add to our understanding of the patient influences on antibiotic use in the Thai setting and can inform strategies for more active patient participation and shared decision-making regarding antibiotic use.